Can Aidi injection restore cellular immunity and improve clinical efficacy in non-small-cell lung cancer patients treated with platinum-based chemotherapy? A meta-analysis of 17 randomized controlled trials following the PRISMA guidelines. Issue 44 (November 2016) - Xiao, Zheng; Wang, Chengqiong; Sun, Yongping; Li, Nana; Li, Jing; Chen, Ling; Yao, Xingsheng; Ding, Jie; Ma, Hu
Abstract: Background: Aidi injection is an adjuvant chemotherapy drug commonly used in China. Can Aidi injection restore the cellular immunity and improve the clinical efficacy in non-small-cell lung cancer (NSCLC) patients treated with platinum-based chemotherapy? There is a lack of strong evidence to prove it. To further reveal it, we systematically evaluated all related studies. We collected all studies about the clinical efficacy and cellular immunity of Aidi injection plus platinum-based chemotherapy for NSCLC in Medline, Embase, Web of Science, China national knowledge infrastructure database (CNKI), Chinese Scientific Journals Full-Text Database (VIP), Wanfang, China biological medicine database (CBM) (established to June 2015), Cochrane Central Register of Controlled Trials (CCRCT) (June 2015), Chinese clinical trial registry, and US-clinical trials (June 2015). We evaluated their quality according to the Cochrane evaluation handbook of randomized controlled trials (RCTs) (5.1.0), extracted data following the patient intervention control group outcomes principles and synthesized the data by meta-analysis. Seventeen (RCTs) with 1390 NSCLC patients were included, with general methodological quality in most trials. The merged relative risk (RR) values and their 95% CI of meta-analysis for objective response rate (ORR) and disease control rate (DCR) were as follows: 1.26 (1.12, 1.42) and 1.11(1.04, 1.17). The merged standardized mean difference (SMD) values and their 95% CI of meta-analysis for the percentage of CD3 + T cells, CD4 + T cells, CD8 + T cells, natural killer (NK) cells, and CD4 + /CD8 + T cell ratio were as follows: 1.41, (0.89, 1.92), 1.59, (1.07, 2.11), 0.85, (0.38, 1.33), 1.64 (0.89, 2.39) and 0.91, (0.58, 1.24). Compared with platinum-based chemotherapy alone, all differences were statistically significant. These results might be overestimated or underestimated. Conclusions: Aidi injection plus platinum-based chemotherapy can improve the clinical efficacy of patients with NSCLC. Aidi injection could significantly restore the cellular immunity damaged by platinum-based chemotherapy. It may be an important tumor immune modulator and protector for patients with NSCLC treated with chemotherapy.